N-(4-Methylphenyl)-2-nitrobenzenesulfonamide - U. Chaithanya; Sabine Foro; B. Thimme Gowda (Acta Crystallographica Section E, 2012)
In the crystal of the title compound, C13H12N2O4S, the conformation of the N—H bond in the –SO2—NH– segment is syn to the ortho-nitro group in the sulfonyl benzene ring. The molecule is twisted at the S—N bond with a torsion angle of 76.55 (18)°. The dihedral angle between the planes of the rings is 72.64 (8)°. In the crystal, molecules are linked by pairs of N—H...O(S) hydrogen bonds to form inversion dimers.